1993
DOI: 10.2307/3869627
|View full text |Cite
|
Sign up to set email alerts
|

Unique Functional Characteristics of the Polymerization and MAP Binding Regulatory Domains of Plant Tubulin

Abstract: An understanding of the regulation of microtubule polymerization and dynamics in plant cells requires biochemical information on the structures, functions, and molecular interactions of plant tubulin and microtubule-associated proteins (MAPs) that regulate microtubule function. We have probed the regulatory domain and polymerization domain of purified maize tubulin using MAP2, an extensively characterized mammalian neumnal MAP. MAP2 bound to the surface of preformed, taxol-stabilized maize microtubules, with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…1 shows that NaCl inhibited eIF-(iso)4F binding to MTs. Because MAP2 binding to plant and animal MTs is little affected by 75 mM KCl (24,25), eIF-(iso)4F binding to MTs must be of relatively low affinity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 shows that NaCl inhibited eIF-(iso)4F binding to MTs. Because MAP2 binding to plant and animal MTs is little affected by 75 mM KCl (24,25), eIF-(iso)4F binding to MTs must be of relatively low affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer sedimentation analysis and EM were as described (25). Protein determinations were done by using dye binding (26) as described (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the similarity of the MAP fraction profiles from each column, bovine tubulin columns were used for all subsequent large scale isolations of MAP fractions because of the ease of purifying high quantities of tubulin from bovine brain and the increased stability of the tubulin columns compared with microtubule columns. The interaction of plant MAPs with animal tubulin has been well documented (35,43,44). Two-dimensional NEPHGE demonstrated that the rice MAP fraction that bound to the bovine tubulin column contained ϳ40 -50 abundant proteins and about 100 less abundant proteins (Fig.…”
Section: Isolation Of a Map Fraction From Developing Rice Seeds-wementioning
confidence: 90%
“…Tubulin prepared from brain has been used because it can be more highly purified in greater yields, and studies on heterologous versus homologous MT-MAP interactions using brain or plant proteins show that either type of interaction produces similar results except for some quantitative variation (Hugdahl et al, 1993;Schellenbaum et al, 1993). Nevertheless, we investigated the interaction of ppSO with taxol-stabilized MTs of pure carrot tubulin.…”
Section: The Carrot Ef-1 a Homolog Also Interacts With Carrot Mtsmentioning
confidence: 99%